Education by Peer to Improve Knowledge About Anemia in Female Student - Nadimin Nadimin (Humanistic Network for Science and Technology (HNST), 2018)
Girls at high risk for anemia. One cause of anemia is the lack of knowledge about how to prevent anemia. Efforts to prevent anemia in adolescents can be done by their peers. This study aimed to determine the influence of counseling by peers on the knowledge of adolescent about anemia. Research carried out by using pretest-posttest without control group design. Data were collected through questionnaires. The results showed an increase in knowledge about anemia and how to prevent it. Before the activity, the proportion of girls who were knowledgeable only 58.8%, then increased to 75%. Suggested extension activities by peers can be developed in other schools, in order to prevent anemia in girls.Keywords: Peers, Knowledge, Anemia